The Importance of Bone Prosthesis in the Identification From Human Skeleton - Koçak, Uğur; Yağan, Murat; Özer, Erdal; Kaçar, Emre (The Bulletin of Legal Medicine, 2014)
In this study, we present a negative identification case, which the claim by the relatives of the exhumed corpse has been invalidated by the macroscopic and Radiologic examination of the skeleton. According to the information obtained via legal documents, a woman died in 2009, another woman died the next day and was buried in the same cemetery. The claimants has suggested that the brother of the other women has forgotten the place of burial, moved their mother’s gravestone elsewhere and constructed a marble grave for his sister. They stated that their mother had total hip replacement surgery in 2006 due to fracture on right side and presented the medical records and x-rays concerning this operation. Both femoral heads were intact and no hip prosthesis was detected neither macroscopically nor on the radiological examination of the exhumed bones. Contrary to the claimant’s suggestions, the postmortem examination of the exhumed bones excluded the possibility of the bones belonging to their mother. So, no further investigation like DNA profiling was performed. Our case indicated that comparison between antemortem and postmortem radiographs has a significant value in identification. Therefore, antemortem radiographs should be kept as long as possible. Keywords: Identification; Forensic Radiology; Bone Prosthesis; Exhumation